GAMBARAN HIGIENE SANITASI INDUSTRI PANGAN RUMAH TANGGA DI WILAYAH KERJA PUSKESMAS BAWANG I - Joko Malis Sunarno Sunarno; Sekar Antik (Unit Penelitian dan Pengabdian Masyarakat, Politeknik Banjarnegara, 2022)
There are 1208 IPRT in Banjarnegara Regency until the end of December 2020, while thosewho have registered and have P-IRT Certificates are 1.030.. The purpose of this study was todetermine the condition of food hygiene and the place of production of the Household Food Industry(IPRT) and to determine the licensing of PIRT in the work area of Puskesmas Bawang 1. This type ofresearch is descriptive with an observational approach. Methods of collecting data throughobservation and interviews using questionnaires and checklists and documentation. Data analysis usedunivariate analysis. The sample in the study was 20 household food industries in the work area ofPuskesmas Bawang I. The characteristics of the handlers are predominantly female, 95%, aged 35-45years, namely 45%, and having graduated from SMA/MA/SMK, namely 45%. The description of theIPRT health environment in the bad category 83%, the description of the IPRT building in the badcategory 56%, the description of the roduction equipment in the bad category 76%, the description ofthe water supply or water supply facilities in the good category 100%, the description of the sanitationhygiene facilities and activities in the bad category 61%, The description of employee health andhygiene in the bad category of 50.8%, the description of the maintenance of the sanitation hygieneprogram in the bad category of 63%, the description of storage in the bad category 92%. Theconclusion of the study shows that IPRT in the Puskesmas Bawang I has not shown overall goodhygiene and sanitation conditions, except for the condition of water supply or water supply facilities,so public health center is expected to be able to carry out training and monitoring of IPRT inaccordance with health standards.